Novel sexual dimorphism in a new genus of Bathynellidae from Russia, with a revision of phylogenetic relationships - Ana I. Camacho; Paloma Mas‐Peinado; Sanda Iepure; Giulia Perina; Beatriz A. Dorda; Adrian Casado; Isabel Rey (Zoologica Scripta, 2020)
Bathynellidae is the neglected family of Bathynellacea, a groundwater group of crustaceans with 33 genera and 107 species described and almost half of them included in the ‘catch‐all’ genus Bathynella . Due to the morphological homogeneity of the species, the taxonomic uncertainties have accumulated over time. Therefore, to explore the phylogenetic relationships among taxa, a combined approach using morphological and molecular data is needed. In this paper, we performed a phylogenetic analysis based on partial sequences of COI and 18S including 30 species of Bathynellidae. This data set represents the most updated one, including a new genus and a new species ( Altainella calcarata gen. n. sp. n.) of Bathynellidae described here from Altai Mountain (Russia). The new taxon presents a new type of sexual dimorphisms with a peculiar structure on the coxopod of the male thoracopod VII and also sexual dimorphism on the mandibular palp, as some species of the subfamily Gallobathynellinae. This is the first species of Bathynellidae that presents both variants of sexual dimorphism. The molecular phylogeny supports the morphology and the erection of the new genus and displays highly divergent genetic units corresponding to subfamilies, with the new genus closer to Bathynellinae genera than other subfamilies. With the description of this new species and its molecular characterization, the existence of the other genera beyond Bathynella is confirmed in Eurasia.